The photography reader history and theory - Wells, Liz 1948- (Routledge, Taylor & Francis Group, 2019)
Focusing on theories of photography, its production, its uses and effects, this reader includes articles by photographers ranging from Edward Weston to Jo Spence, as well as key thinkers like Roland Barthes and Susan Sontag.